The Community Empowerment Based Conservation Program Development Strategy in the Cycloop Mountain Nature Reserve: The Development Strategy of the Community Empowerment Based Conservation Program in the with Fostered Village Models and Conservation Partnerships In the Cycloop Mountains Nature Reserve - Lumban Gaol, Chandra (Prospect Publishing, 2024)
The community-based conservation program with the Foster Village Model and Conservation Partnership in the Cycloop Mountains Nature Reserve (CAPC) has not gone well, requiring the development of a more effective strategy for its implementation. This paper aims to analyze public perceptions, measure community participation, describe and assess implementation, identify supporting and inhibiting factors, and formulate development strategy directions. This paper was conducted using a qualitative approach with descriptive analysis and SWOT analysis. The results of the writing show that 1) community perceptions of community empowerment programs are in the